An Assessment on Factors Affecting Student –Teachers’ Inferential Understanding in Reading Comprehension Practice: The Case of GilgelBeles College of Teacher Education, BenishangualGumuz Region - Basizew, Shewa (International Journal of Social Sciences and Management, 2017)
This study aimed to assess, identify and analyze factors affecting student-teachers’ inferential understanding in the reading comprehension practices in the English department of GilgelBeles College of teachers Education in BenishangulGumuz Regional State. It attempted to answer the following basic questions: - what factors influence inferential understanding,and how they influence inferential understanding. In order to achieve the objectives, a sample population is taken from the student-teachers and all three English language teachers in the department. Data collection instruments included questionnaire, interview and classroom observation. The collected data was analyzed quantitatively for close ended questions and qualitatively for open-ended questions, interviews and classroom observations. The study reveals that the main impediments that hinder student-teachers’ inferential understanding while practicing for reading comprehension are lack of regular practice, poor high school background knowledge , the physical environment ( high temperature) , lack of motivation, large class size and lack of teacher commitment in supporting students, loss of attention towards implied meanings and problem of using reading strategies effectively. The studies also indicate that, student –teachers need to develop their motivation and to practice reading activities more frequently. Furthermore, teachers need to commit to providing their students with more practice making use of authentic materials. In addition, installing fans in college classrooms would improve learning conditions and building more classrooms would help limit the number of students in a class. Int. J. Soc. Sc. Manage. Vol. 4, Issue-2: 148-153